Peranan Guru Pendidikan Agama Kristen Sebagai Model dan Teladan Terhadap Penanaman Integritas Moral Peserta Didik di SMA Reformasi Plus Kelas XI IPA - Dominggus Umbu Dingu; Prihadi Kristiyan; Yublina Tefa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2021)
Development to achieve educational goals certainly leads to instruments that are responsible for the implementation. The teacher is the instrument, which is required to bring out all the potential possessed, both knowledge and review of self-aspects as a reflection that should be imitated. Thus, it is absolutely necessary to have a complete personality professionalism and role model points that are certainly inherent in every teacher. Teachers are required to maintain stability in speaking and acting as a reaction to the practice of integrity values that do not know place, time and situation. The personality in question does not create a chasm to limit oneself in interacting with others, but how the whole existence can be a role model. School is a place of interaction in the daily life of a teacher, here the teacher does what is his responsibility and obligation in fostering students (towards the desired goal). The implementation pattern certainly requires good performance starting from personality, discipline and how a teacher can be relied on and become a role model for students. The moral integrity of students is the expectation of a teacher, of course. In relation to this review, a teacher, especially a PAK teacher, is required and of course has a very strategic and core role in the implementation of the process of forming moral integrity as a role model for students.